PERANCANGAN SISTEM AUDIT MUTU INTERNAL BERBASIS WEB STUDI KASUS BADAN PENJAMINAN MUTU UNMAHA - Muhammad Romzi; Budi Kurniawan (Universitas Mahakarya Asia, 2025)
Abstract – Internal Quality Audit (IQA) is an essential instrument in the quality assurance cycle of higher education institutions as part of the PPEPP process (Establishment, Implementation, Evaluation, Control, and Improvement). At Mahakarya Asia University (Unmaha), the implementation of IQA relies on Google Forms and Google Sheets as media for data collection and findings recapitulation. The use of these platforms has several limitations, such as the absence of an integrated audit process, weak data validation, potential duplication of entries, error-prone findings recapitulation, and difficulties in systematically monitoring follow-up actions. These conditions result in longer audit processes, inefficiencies, and hinder the availability of fast, accurate, and well-documented quality reports. This study aims to design a web-based IQA system capable of supporting a structured, integrated, and fully documented audit process. The method used is the Design Science Research approach, which includes problem identification, needs analysis, system specification development, business process modeling, and system modeling using the Unified Modeling Language (UML). The data requirements were collected through a review of standard IQA instruments, interviews with auditors, and analysis of the university’s Quality Assurance System (SPMI) documents. The results of this study include a system design consisting of functional and non-functional requirements, use case models, activity diagrams, sequence diagrams, and a database design to support the audit process, findings management, follow-up monitoring, and automatic report generation. This design is expected to improve the efficiency of IQA implementation, minimize recording errors, strengthen audit accountability, and support the development of a sustainable quality culture within the university.